2015
DOI: 10.1002/ece3.1852
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the influences of mean body size and size structure on ecosystem functioning: an example of nutrient recycling by a non‐native crayfish

Abstract: Body size is a fundamental functional trait that can be used to forecast individuals' responses to environmental change and their contribution to ecosystem functioning. However, information on the mean and variation of size distributions often confound one another when relating body size to aggregate functioning. Given that size‐based metrics are used as indicators of ecosystem status, it is important to identify the specific aspects of size distributions that mediate ecosystem functioning. Our goal was to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…For instance, the ingestion rate and speed of movement of an individual are correlated with its body size (Peters, 1983). Also, shifts in body size structure of communities have been shown to affect ecosystem functioning (Fritschie & Olden, 2016;Yvon-Durocher & Allen, 2012). Hence, body size can be considered a super trait (Brose et al, 2017;Fritschie & Olden, 2016) relating to both ecological effects and responses and therefore constraining ecological and evolutionary dynamics (Applebaum, Pan, Hedgecock, & Manahan, 2014;Llandres et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ingestion rate and speed of movement of an individual are correlated with its body size (Peters, 1983). Also, shifts in body size structure of communities have been shown to affect ecosystem functioning (Fritschie & Olden, 2016;Yvon-Durocher & Allen, 2012). Hence, body size can be considered a super trait (Brose et al, 2017;Fritschie & Olden, 2016) relating to both ecological effects and responses and therefore constraining ecological and evolutionary dynamics (Applebaum, Pan, Hedgecock, & Manahan, 2014;Llandres et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Such a research gap points to an underrated consequence of climate change, as shifts in body size distribution even within a single species have the potential to affect ecosystem functioning (Dossena et al . ; Fritschie & Olden ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether smaller soil invertebrates such as nematodes would also experience a similar body size shift in response to FTCs remains unknown. Such a research gap points to an underrated consequence of climate change, as shifts in body size distribution even within a single species have the potential to affect ecosystem functioning (Dossena et al 2012;Fritschie & Olden 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that variably sized (or size‐structured) populations produce different ecological consequences than do homogeneous populations (e.g., Asquith & Vonesh, ; Fritschie & Olden, ; Kishida, Mizuta, & Nishimura, ; Peacor & Werner, ; Rudolf & Rasmussen, ; Yamaguchi & Kishida, ). Such studies have tended to focus on distinct age classes, such as cohorts from different breeding events (e.g., Peacor & Werner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecologists typically focus on average (mean) values of traits within species when characterizing functional trait diversity (Cianciaruso, Batalha, Gaston, & Petchey, 2009;Fritschie & Olden, 2016). However, within a single species, individuals exhibit significant variability in ecologically relevant phenotypic traits.…”
mentioning
confidence: 99%